1983
DOI: 10.1021/bi00294a024
|View full text |Cite
|
Sign up to set email alerts
|

Location of an essential carboxyl group along the heavy chain of cardiac and skeletal myosin subfragments 1

Abstract: Cardiac and skeletal myosin subfragments 1 cleaved into three fragments were modified by 1-cyclohexyl-3-(2-morpholinoethyl)carbodiimide metho-p-toluene-sulfonate in the presence of the nucleophile nitrotyrosine ethyl ester. The effects observed (first-order kinetics of ATPase inactivation, incorporation of 1 mol of nitrotyrosine/mol of subfragment 1) were similar to those previously observed for the nondigested subfragments 1 [Lacombe, G., Van Thiem, N., & Swynghedauw, B. (1981) Biochemistry 20, 3648-3653; Kör… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Recently the substructure of cardiac SF1 has been investigated by examining the course and extent of tryptic cleavage. These studies showed that the cardiac SF1 is attacked at essentially the same two restricted regions of its associated heavy chain as was found previously for skeletal SF1 (Flink & Morkin, 1982;Korner et al, 1983) and results in a tryptic SF1 species comprised of the light chain and the three protease-resistant fragments of about 27K, 50K, and 21K arranged in this order in the linear sequence. These findings suggest that the conformation of the cardiac protein bears a high degree of similarity to that of skeletal SF1.…”
supporting
confidence: 75%
“…Recently the substructure of cardiac SF1 has been investigated by examining the course and extent of tryptic cleavage. These studies showed that the cardiac SF1 is attacked at essentially the same two restricted regions of its associated heavy chain as was found previously for skeletal SF1 (Flink & Morkin, 1982;Korner et al, 1983) and results in a tryptic SF1 species comprised of the light chain and the three protease-resistant fragments of about 27K, 50K, and 21K arranged in this order in the linear sequence. These findings suggest that the conformation of the cardiac protein bears a high degree of similarity to that of skeletal SF1.…”
supporting
confidence: 75%
“…The observation that the rate of thermal inactivation of the ATPase of SI appears to parallel the decay of the 50-kDa fragment (Figure 4) suggests that the integrity of the 50-kDa segment is crucial for this function as suggested by Setton and . A number of recent studies based on chemical modification (Korner et al, 1983;Hiratsuka, 1986b), proteolysis (Chaussepied et al, 1986a,b), and photoaffinity labeling (Mahmood & Yount, 1984) have pointed to the importance of this region to the ATPase function. Moreover, it is known that this segment also provides a contact with actin in both the absence and presence of nucleotide (Yamamoto & Sekine, 1979b;Mornet et al, 198 la,b;Chen et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…A specific modification of serine 324 was revealed by a nucleotide analog containing a reactive group instead of its ribose ring (Nakamaye et al, 1985;Yount, et al, 1987). A carboxyl group was specifically modified and identified as residing in this fragment; its modification led to the loss of ATPase activities (Korner et al, 1983). The fluorescent reagent 4-flu0ro-7-nitrobenz-2-oxal,3-diazole was also incorporated and reacted selectively with two lysyl residues in this fragment (Hiratsuka, 1986a).…”
Section: The 50k Sequencementioning
confidence: 99%